BIM performance framework for the maintenance and refurbishment of housing stock. Issue 3 (11th July 2016) - Alwan, Zaid
Abstract : Purpose: – The purpose of this paper is to present a systematic framework for maintenance and refurbishment in domestic housing sector for utilising BIM processes, which tackles ageing housing stock and allows for sustainability improvements, and carbon footprinting. Design/methodology/approach: – The methods used consisted using modern technology currently used in the built environment sector, and applying them to BIM framework. The BIM implementation covered both technical and social implications, and appraisal of different approaches needed to make the framework effective within the housing sector. Findings: – The study revealed that there are many modern approaches for a BIM framework in relation to maintenance and refurbishment, and a possible strategic BM approach largely used in new built sector can be applied to domestic building to achieve effective modern asset management. This makes the housing stock easier to manage as well as addressing vital issues such as carbon footprint, and excessive energy wasted on inefficient buildings envelopes. Research limitations/implications: – Further testing and adoption of the approach and model proposed, will result in greater acceptance of BIM for housing management and greater realisation of benefits. Practical implications: – A potential model that can be used and applied to domestic housing sector as a result of this research. Originality/value: – Demonstration of a road map for BIM applications within the maintenance and refurbishment for housing stock is currently under researched, and the findings aimed to address such a gap. This can in turn shift the focus of BIM towards asset management and building performance rather than just new build.